Sturuktur Ukuran Dan Musim Penangkapan Madidihang (Thunnus Albacares) Hasil Tangkapan Huhate Di Perairan Selatan Pulau Buton - Wa Ode Sitti Hardian Sari; Ahmad - Mustafa; Syamsul - Kamri; Hasnia - Arami; Naslina - Alimina (Universitas Halu Oleo, 2021)
Yellowfin tuna (Thunnus albacares) is one of the important commodities for the fishing industry in Indonesia. Some of these commodities are caught by means of using FADs as fishing aids. This study aims to determine the composition of the size and season of yellowfin tuna fishing in the southern waters of Buton Island. The study was conducted at the Wameo Fish Landing Base, Baubau City from April to June 2021. The fork length of yellowfin tuna was measured and then presented in the form of a frequency distribution. Yellowfin fishing season was analyzed using the Fishing Season Index, based on the number of catches per monthly fishing effort for the last 3 years (2018 to 2020). The results showed that the size range of yellowfin tuna caught was 32-67.5 cmFL or all of them belonged to juvenile size. The dominant length class (76%) was in the range of 37-46 cmFL. The value of the fishing season index shows that the yellowfin catching season occurs from January to February, April to May, and September.